Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 7 - Algebraic Fractions - Chapters 1-7 Cumulative Review Problem Set - Page 324: 8



Work Step by Step

We evaluate the expression by substituting $x=4$ throughout the expression and simplifying: $\frac{x^{2}+3x-10}{x^{2}-9x+14}$ =$\frac{(4)^{2}+3(4)-10}{(4)^{2}-9(4)+14}$ =$\frac{16+12-10}{16-36+14}$ =$\frac{28-10}{-20+14}$ =$\frac{18}{-6}$ =$-3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.